2023
DOI: 10.1109/access.2023.3272053
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Attack Graph Analysis for IoT Vulnerability Assessment: Challenges, Open Issues, and Future Directions

Abstract: Vulnerability assessment in industrial IoT networks is critical due to the evolving nature of the domain and the increasing complexity of security threats. This study aims to address the existing gaps in the literature by conducting a comprehensive survey on the use of attack graphs for vulnerability assessment in IoT networks. Attack graphs serve as a valuable cybersecurity tool for modeling and analyzing potential attack scenarios on systems, networks, or applications. The survey covers the research conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Various methods are available for assessing and detecting attacks to improve the security of the IoT. Attack graphs combined with other methods, such as game theory and machine learning, help assess the vulnerability of IoT networks [103]. Recent research focuses on using deep learning methods to design malware detection systems [104].…”
Section: ) Attack Assessment and Detectionmentioning
confidence: 99%
“…Various methods are available for assessing and detecting attacks to improve the security of the IoT. Attack graphs combined with other methods, such as game theory and machine learning, help assess the vulnerability of IoT networks [103]. Recent research focuses on using deep learning methods to design malware detection systems [104].…”
Section: ) Attack Assessment and Detectionmentioning
confidence: 99%
“…GAs are metaheuristics that mimic the Darwinian evolutionary process, wherein the fittest individuals are more likely to transmit their traits to the next generation. GAs have been applied successfully to a variety of problems such as vulnerability assessment [32,33], protection coordination [34,35], expansion planning [36,37], etc. Furthermore, it has been demonstrated that GAs are effective in addressing the problem of UFLS scheme dimen-sioning, as indicated in [38][39][40].…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…It reveals all potential vulnerability combinations and their relationships and lists all potential attack paths from the perspective of the attacker to reflect the security state of the network, such as the number of attack paths, the length of the shortest attack path, and the key vulnerability. Multi-step attacks can be effectively prevented based on the attack graph [11,12]. To enhance the relevance between vulnerability assessment and network systems, many studies have conducted network vulnerability analysis based on attack graphs.…”
Section: Introductionmentioning
confidence: 99%